Gravitacijski valovi - Mohorič, Aleš (Obzornik za matematiko in fiziko, 2017)
The article outlines a short history of gravitational wave detection. Fundamental properties of waves and its detection are described. Recent successful detections show a great potential of gravitational astronomy.
Keywords: gravitacija; gravitacijski valovi; gravitavijsko polje; interferometri; Maxwellove enačbe; teorija relativnosti